Fractional PID controlled cascaded flyback switched mode power supply with enhanced time domain response - K. Sasikala; R. Krishna Kumar (Institute of Advanced Engineering and Science, 2019)
This work compacts with the modeling, simulation, and application of a Fractional Order Proportional Integral Differential (FOP-I-D) controlled Cascaded Flyback Switched Mode Power Supply (CFSMPS) system. It recommends Parallel cascaded flyback converter for the production of essential DC voltage from the input supply voltage. The output from CFSMPS is regulated by using closed loop configuration. The simulation of Closed-loop Proportional-Integral (PI) and FOP-I-D controlled CFSMPS system has been done and the results of the systems are related. The outcomes signify that the FOP-I-D based system has presented an enhanced response to represent as similar to the PI controlled CFSMPS system. The FOP-I-D controlled CFSMPS system has benefits like decreased steady-state error and enhanced time-domain response.